The Spanish Core Collection of Common Beans (Phaseolus vulgaris L.): An Important Source of Variability for Breeding Chemical Composition - Rivera, Ana; Plans, Marçal; Sabaté, Josep; Casañas, Francesc; Casals, Joan; Rull, Aurora; Simó, Joan (Frontiers in Plant Science, 2018)
The Iberian Peninsula is considered a secondary centre of diversity for the common bean, and the Spanish National Plant Genetic Resources Centre’s germplasm bank holds more than 3,000 Spanish accessions of Phaseolus vulgaris L. from which a core collection of 202 landraces has been selected. In order to encourage the use of this abundant resource, this study aimed to characterise genetic diversity, by measuring chemical composition in these core collection (in both the seed coat and cotyledon) using previously developed near infrared spectroscopy models. Crucially, these landraces in question all originated under similar agroclimatic conditions, allowing these field trials to be conducted in a single location without significantly altering the agronomic behaviour of individual accessions. Using previously reported data, we also explored the correlations between chemical composition and culinary/sensory traits, as well as possible associations between chemical composition and seed coat color or gene pool (Middle American or Andean). The general Mahalanobis distance was > 3 in only 11 of 1,950 estimations, confirming the robustness of the regression models previously developed. Variability was greater in seed coat than in cotyledon compounds and ranges for all compounds were wide: ash 34-94 g kg-1, Ca 5-31 g kg-1, dietary fiber 554-911 g kg-1, Mg 2-4.4 g kg-1, uronic acid 95-155 g kg-1, protein 192-304 g Kg-1, starch 339-446 g Kg-1, amylose 208-291 g Kg-1, amylopectin 333-482 g Kg-1, and apparent amylose 241-332 g Kg-1. Accessions with white seed coats tended to be richer in ash, dietary fiber, uronic acid and Ca, and accessions of the Middle American gene pool had on average 65% more Ca than the Andean gene pool. Strong genetic correlations were not identified between chemical and culinary/sensory traits. This is particularly positive with regards to plant breeding, as it means that the exploitable variability in chemical composition that we have identified here is largely free of pleiotropic effects or gene-linkage that could potentially result in negative collateral effects of selection. The genetic diversity of chemical composition described in the Spanish core collection of beans therefore represents a promising opportunity to develop cultivars with superior nutritional profiles.